Webqual 4.0 Analysis of Java Dancer Resto and Café Ordering Website - Nur Iman, Rizki; Jibril, Muhammad; Khoiriyah, Rizqiyatul; Pakaja, Fachrudin (LPPM STIKI MALANG, 2025)
Java Dancer Resto and Cafe is one of the restaurants in Malang City that has utilized a website as a means of online ordering, this study aims to analyze the quality of usability, information, interaction services, and the overall ordering website of Java Dancer Resto and Cafe using the WebQual 4.0 method. The research method is quantitative descriptive using a survey method to 100 consumers, data analysis using the average and percentage of user satisfaction with the Kaplan and Norton interval scale. The results showed that the overall quality of the Java Dancer Resto and Cafe ordering website was considered very good by users with an average score of 4.34. The usability aspect received the highest rating with a score of 4.41, indicating ease of use and intuitive navigation. The quality of information received a score of 4.35, indicating high accuracy and relevance of information. The service interaction aspect received a score of 4.25 and is still in the very good category, but requires improvement, especially in service personalization and transaction security.